Distinct Cardiac Connexin-43 Expression in Hypertrophied and Atrophied Myocardium May Impact the Vulnerability of the Heart to Malignant Arrhythmias. A Pilot Study - Szeiffova Bacova, B; Andelova, K; Sykora, M; T, Egan Benova; Kurahara, L H; Slezak, J; Tribulova, N (Physiological research, 2023)
Our and other studies suggest that myocardial hypertrophy in response to hypertension and hyperthyroidism increases propensity of the heart to malignant arrhythmias, while these are rare in conditions of hypothyroidism or type-1 diabetes mellitus associated with myocardial atrophy. One of the crucial factors impacting the susceptibility of the heart to life-threatening arrhythmias is gap junction channel protein connexin-43 (Cx43), which ensure cell-to-cell coupling for electrical signal propagation. Therefore, we aimed to explore Cx43 protein abundance and its topology in hypertrophic and hypotrophic cardiac phenotype. Analysis were performed in left ventricular tissue of adult male spontaneously hypertensive rat (SHR), Wistar Kyoto rats treated for 8-weeks with L-thyroxine, methimazol or strepotozotocin to induce hyperthyroid, hypothyroid and type-1 diabetic status as well as non-treated animals. Results showed that comparing to healthy rats there was a decrease of total myocardial Cx43 and its variant phosphorylated at serine368 in SHR and hyperthyroid rats. Besides, enhanced localization of Cx43 was demonstrated on lateral sides of hypertrophied cardiomyocytes. In contrast, total Cx43 protein and its serine368 variant were increased in atrophied left ventricle of hypothyroid and type-1 diabetic rats. It was associated with less pronounced alterations in Cx43 topology. In parallel, the abundance of PKCepsilon, which phosphorylates Cx43 at serine368 that stabilize Cx43 function and distribution was reduced in hypertrophied heart while enhanced in atrophied once. Findings suggest that differences in the abundance of cardiac Cx43, its variant phosphorylated at serine368 and Cx43 topology may explain, in part, distinct propensity of hypertrophied and atrophied heart to malignant arrhythmias.
Keywords: diabetes mellitus 1. typu; potkani inbrední WKY; Male; konexiny; Connexins; hypertyreóza; atrofie; experimentální diabetes mellitus; Hyperthyroidism; pilotní projekty; potkani inbrední SHR; Myocardium; mužské pohlaví; srdeční arytmie; hypertrofie; Arrhythmias, Cardiac; krysa rodu Rattus; Atrophy; Animals; Hypothyroidism; zvířata; Rats; Rats, Inbred SHR; konexin 43; Connexin 43; Diabetes Mellitus, Type 1; Diabetes Mellitus, Experimental; Hypertrophy; Pilot Projects; Rats, Inbred WKY; myokard; hypotyreóza